2011
DOI: 10.4049/jimmunol.1003523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence thatCd101Is an Autoimmune Diabetes Gene in Nonobese Diabetic Mice

Abstract: We have previously proposed that sequence variation of the CD101 gene between NOD and C57BL/6 (B6) mice accounts for the protection from type 1 diabetes (T1D) provided by the Idd10 region, a <1 Mb region on mouse chromosome 3. Here, we provide further support for the hypothesis that Cd101 is Idd10 using haplotype and expression analyses of novel Idd10 congenic strains coupled to the development of a CD101 knockout mouse. Susceptibility to T1D was correlated with genotype-dependent CD101 expression on multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 34 publications
7
55
0
Order By: Relevance
“…Analyses of additional Idd10 NOD congenic strains, NOD.A/J Idd10 and NOD.CAST Idd10 , confirm the correlation of differential control of T1D (44, 47) and PBC with Cd101 gene expression. A newly developed CD101-deficient B6 knockout strain develops PBC with similar severity to that observed in NOD.B6 Idd10 mice and significantly more severe liver disease than parental NOD and B6 mice.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Analyses of additional Idd10 NOD congenic strains, NOD.A/J Idd10 and NOD.CAST Idd10 , confirm the correlation of differential control of T1D (44, 47) and PBC with Cd101 gene expression. A newly developed CD101-deficient B6 knockout strain develops PBC with similar severity to that observed in NOD.B6 Idd10 mice and significantly more severe liver disease than parental NOD and B6 mice.…”
Section: Introductionmentioning
confidence: 65%
“…Here, we show that the B6-derived Idd10 region present in NOD.B6 Idd10 mice primarily accounts for the increased PBC risk of NOD.B6 Idd10/18 congenic mice upon infection and correlates with genotype-dependent protein expression of Cd101 , the primary T1D candidate gene of the Idd10 region (4447). Analyses of additional Idd10 NOD congenic strains, NOD.A/J Idd10 and NOD.CAST Idd10 , confirm the correlation of differential control of T1D (44, 47) and PBC with Cd101 gene expression.…”
Section: Introductionmentioning
confidence: 74%
“…Genetic mapping and gene-phenotype studies in mice and humans have revealed that, in addition to the MHC locus, more than 20 insulin-dependent diabetes (Idd) loci contribute to T1D development (7). One of these loci, the Idd10 locus on mouse chromosome three, contains the B7x gene (8), suggesting a potential role of B7x in T1D. Murine studies support this notion as B7x suppresses CD4 T cell-mediated T1D (4).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted consequence of B6/BALB coding nonsynonymous genetic variation was assessed using SIFT (29) (http://sift.jcvi.org/), PANTHER (30) (http:/www.pantherdb.org/), and PolyPhen (31) (http://genetics.bwh.harvard.edu/pph/) algorithms. This approach to candidate gene identification has been used by others (32)(33)(34).…”
Section: Candidate Gene Identificationmentioning
confidence: 99%